Sound environment in an urban apartment building during and after the COVID-19 lockdown - Yang, Tingting; Kang, Jian (Frontiers in Psychology, 2023)
Quiet areas, such as quiet communities, are encouraged to maintain a harmonious and peaceful urban living environment, and the design approach has drawn increasing attention in recent years. Related residential standards define the thresholds of quietness concerning noise pollution problems. However, the variation in height across floors of high-rise buildings and time in sound environments have not been detailed. The city of Shanghai experienced a citywide lockdown to contain the spread of COVID-19 showing the evidence of quietness with marked reductions in anthropogenic noise. Here, we conducted noise monitoring in a 14-story apartment building surrounded and shielded by other buildings in a typical urban community during and after lockdown. The mean value of all 14 floors of equivalent continuous A-weighted sound pressure level (LAeq) after lockdown was larger than that during lockdown, and the differences were 3.6 and 3.1 dB during the daytime and night-time periods, respectively. The values of LAeq at low heights were slightly smaller than those at high heights during and after lockdown. The variations due to heights were not great; however, the changing tendency from ground to top floor was similar and correlated during and after lockdown. The difference between the maximum and minimum values of the floors was 3 dB during the daytime period and 4.5 to 5.1 dB during the night-time period. The day equivalent continuous A-weighted sound pressure level (Lday) and the night equivalent continuous A-weighted sound pressure level (Lnight) at the middle height of the building increased 4.0 and 1.3 dB after lockdown, respectively. The changing tendency of LAeq during a daily cycle during and after lockdown was similar and highly correlated. The differences of frequency characteristics of noise level were larger in the range from 63 to 2000 Hz. We suggest that the building presents a typical quiet living condition in high-density habitats in China; that is, the difference is approximately 3 to 4 dB, and the patterns of variation in height and time are similar between the absence and limited presence of anthropogenic noise. In practice, it would be useful to consider specific floor level or time of day.